Anti-Cryptosporidium parvum activity of Artemisia judaica L. and its fractions: in vitro and in vivo assays - Ahmed, Shahira A.; Eltamany, Enas E.; Nafie, Mohamed S.; Elhady, Sameh S.; Karanis, Panagiotis; Mokhtar, Amira B. (Frontiers in Microbiology, 2023)
(1) Background: This study investigates the toxic activity of Artemisia judaica ethanolic extract (ArEx) as well as its phenolic fraction (ArPh), and terpenoid fraction (ArT) against Cryptosporidium parvum (C. parvum) oocysts. (2) Methods: Estimation of the total phenolic (TPC), total flavonoids (TFC), and total terpenoids contents (TTC) in ArEx; investigation of the in vitro antioxidant activity of ArEx, ArPh, and ArT; evaluation of ArEx, ArPh, and ArT toxic activity against C. parvum oocysts using MTT assay; on ArPh-treated C. parvum oocysts, parasitological analyses and comet assay were performed both in vitro and in vivo (infectivity) (3) Results: The ArEx TPC, TFC, and TTC was 52.6±3.1 mgGAE/g, 64.5±3.1 mg QE/g, and 9.5±1.1 mg Linol/g respectively. Regarding the phytochemical in vitro antioxidant activity, the ArPh exhibited the highest antioxidant activity compared to the ArEx and ArT. The ArPh showed promising free radical scavenging activity of DPPH and ABTS•+ with IC50 values of 47.27±1.86 µg/mL and 66.89±1.94 µg/mL, respectively. Moreover, the FRAP of ArPh was 2.97±0.65 mMol Fe+2/g while its TAC was 46.23±3.15 mg GAE/g. The ArPh demonstrated toxic activity against C. parvum oocysts with a potent IC50 value of 31.6 µg/mL compared to ArT (promising) and ArEx (non-effective). ArPh parasitological analysis demonstrated MIC90 at 1000 µg / ml and effective oocysts destruction on count and morphology. ArPh fragmented oocysts nuclear DNA in comet assay. Beginning at 200 µg/mL, ArPh-treated oocysts did not infect mice. (4) Conclusions: To combat C. parvum infection, the phenolic fraction of A. judaica L. shows promise as an adjuvant therapy or as a source of potentially useful lead structures for drug discovery.